Effect of Inflation, Exports, and Employment on Economic Growth in Central Java - Queen Pamela; Lucia Rita Indrawati (LifeSciFi, 2022)
Economic growth is closely related to the community's welfare; therefore, economic growth is one of the government's priorities. There are many factors that can affect economic growth. This study analyzes the effect of inflation, exports, and employment on the economic growth of Central Java Province from 1994-2019. The error correction model (ECM) with E-views 10 software is used. The test results show that the inflation variable significantly affects economic growth in the long and short term. In contrast, export variables do not affect long-term and short-term economic growth. The variables of the working population also do not affect economic growth in the long and short term. This research uses secondary data. Secondary data has a weakness; namely, the results of the study may not be able to answer the question. In addition, research results are only oriented to the value and amount of data processing. The study suggests that the government build and develop regional exports with long-term economic growth. It is also recommended that future studies take other variables to add insight related to economic growth in Central Java.